PENINGKATAN KOMPETENSI PETUGAS ARSIP SMK SWASTA SEKABUPATEN KENDAL MELALUI DIGITALISASI ARSIP BERBASIS 8 STANDAR NASIONAL PENDIDIKAN - Nina Oktarina; Joko Widodo; Murwatiningsih; Edy Suryanto (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
The main problem of the non-optimal management of digital-based records in schools is school archive officers' lack of knowledge and skills. The service activity aims to increase knowledge related to digital-based school archive management and improve digital-based school archive management skills by using the National Education Standard 8-Based Digital Archive Application. This service activity targets the archive or administrative officer at Private Vocational Schools, as many as 25 people throughout Kendal Regency. Service activities use two main methods, namely lectures and direct practice. This service activity has fulfilled three aspects of success, namely: 1) all participants participated in the entire series of activities well, 2) all participants were actively involved during the activity, and 3) more than 50% of participants were able to practice archive management using the 8-Based Digital Archive Application. National Education Standards.